RETHINKING HOW WE DO ENVIRONMENTAL SCIENCE - Malayang III, Ben S. (Silliman Journal, 2022)
This paper examines 17 reviews of various philosophical, conceptual and methodological issues and experiences with environmental interdisciplinary work. These were presented and read in the 6th International Conference on Environmental Future, on Interdisciplinary Progress in Environmental Science and Management, held in Newcastle University, UK, July 18-22, 2011. The 17 reviews are examined for indications of the current progress and direction of the development of interdisciplinary approaches to environmental research and governance. The implications of interdisciplinarity to sustainability (or how environmental interdisciplinarity contributes to improving the geospheric, biospheric and ethnospheric well-being in our planet) are drawn from the reviews.